Detection of classical Hodgkin lymphoma specific sequence in peripheral blood using a next‐generation sequencing approach. (29th March 2015) - Oki, Yasuhiro; Neelapu, Sattva S.; Fanale, Michelle; Kwak, Larry W.; Fayad, Luis; Rodriguez, Maria A.; Wallace, Michael; Klinger, Mark; Carlton, Victoria; Kong, Katherine; Faham, Malek; Younes, Anas
Summary We applied a highly sensitive next‐generation sequencing method to identify lymphoma‐specific immunoglobulin gene segments in classical Hodgkin lymphoma (CHL) at initial diagnosis or recurrence, and assessed the ability of detecting such lymphoma‐specific sequences in peripheral blood (PB). Seventeen CHL cases were tested and lymphoma‐specific sequences were identified in 12 of the primary tumour biopsies. In 11 of these patients whose paired PB samples were available, tumour‐specific clonotypes were detected in PB in eight patients. This data demonstrates the feasibility of detecting circulating tumour‐specific sequences, creating an unprecedented opportunity to optimize the future treatment and monitoring strategies for patients with CHL.